PENERTIBAN GENG MOTOR DI KOTA PEKANBARU TAHUN 2012 – 2013 (STUDI KEBIJAKAN KETERTIBAN UMUM PEMERINTAH KOTA) - Muhammad Wira Dharmika; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this present research was to analyze the Regulation of Geng Motor in Pekanbaru Year 2012-2013 (Study of City Government at Public Policy Procedure). Cruelness which was done by geng motor in Pekanbaru really fidgety society and rise victims, so the researcher interested to analyze the regulation of geng motor. The problems in this research were; what factor because geng motor show up, why perda number 5 year 2002 did not optimal, and why perda was not synergy to prevent public procedure.Qualitative research was used in this research. The collected data were analyzed by descriptive. This research used observation document and interview with informant. The data was primary and secondary from observation and interview.Based on this research of regulation of geng motor in Pekanbaru year 2012-2013 (study of city government at public policy procedure) is suggest that happen because identity crisis of teen, bad influence from age friend, weak of self-control, community and bad environment. Problem of geng motor not only classing public procedure but also include in law area and have to act undoubtful by officers in this problem is policy. Government should do preventive way and policy should do technically.Key note : Regulation, Wisdom, Geng Motor